LEXICO-SYNTACTICAL STYLISTIC DEVICES: SIMILE, PERIPHRASIS, LITOTES, GRADATION, ANTITHESIS, AND REPRESENTED SPEECH - Sotvoldiyeva Nozima; G’ofurova S.M (TADQIQOTLAR, 2026)
Annotation This article discusses the nature of lexico-syntactical stylistic devices as a specific category in linguistics. It examines the aims and functions of devices such as simile, periphrasis, litotes, gradation, antithesis, and represented speech. Special attention is paid to how these means intensify speech and create a stylistic effect in modern English.